2016
DOI: 10.4103/2230-8210.192903
|View full text |Cite
|
Sign up to set email alerts
|

Trimester-specific reference interval for thyroid hormones during pregnancy at a Tertiary Care Hospital in Haryana, India

Abstract: Background:Reference intervals for thyroid hormone during pregnancy need to be gestational age, method, and population specific and there is need to establish trimester-specific thyroid levels for the different population across the world. The aim of this study was to establish trimester-specific reference range for thyroid hormone during pregnancy in a tertiary care center in Haryana.Materials and Methods:A total of 1430 pregnant women were recruited for the study. Participants having any history of chronic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…In addition, sample size, representativeness of the reference population and the manufacturer's immunoassay methodology also have an important impact on the reference interval [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sample size, representativeness of the reference population and the manufacturer's immunoassay methodology also have an important impact on the reference interval [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in China it has been shown that prevalence of subclinical hypothyroidism using laboratory trimester specific ranges for TSH was 4% in pregnant women during the first trimester whereas this prevalence was 27.8% when a diagnostic criterion of TSH > 2.5 mU/L was used [21]. Moreover, many reported trimester-specific reference intervals for TSH were different from those recommended by 2011 ATA guidelines [22] [23]. It is therefore probable that, in our study, hypothyroidism frequency determined following 2011 ATA guidelines was overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…One was excluded in view of poor quality. Sevens studies are published manuscripts[ 13 14 15 16 20 21 22 ] while one study was poster at an endocrine conference (Choudhary et al .) [ Table 1 ].…”
Section: R Esultsmentioning
confidence: 99%
“…TSH was measured by different assay methods which include electrochemiluminescence,[ 13 15 20 ] enzyme-linked immunosorbent assay,[ 14 ] enzyme immunoassay,[ 21 ] and chemiluminescence immunoassays. [ 16 22 ]…”
Section: R Esultsmentioning
confidence: 99%